Antioxidative activity of apple skin or flesh extracts associated with fruit development on selected apple cultivars - Kondo, S.; Tsuda, K.; Muto, N.; Ueda, J. E.
The antioxidative activity of skin or flesh extracts and the polyphenolic composition during the fruit development were examined in three different cultivars of apple (Malus sylvestris (L.)Mill. var. domestica (Borkh.)Mansf.); 'Fuji' with red skin, 'Oorin' with yellow skin, and 'Redfield', a cider apple. The IC50 values of superoxide (O2?)and 1-diphenyl-2-picrylhydrazyl (DPPH)-radical-scavenging activities remained low throughout fruit development in the skin of the three cultivars. The IC50 values of the activities in the flesh of 'Fuji' and 'Oorin' were low at the beginning, but increased toward the ripening stage. In contrast, the IC50 values of the activities in the flesh of 'Redfield' remained low throughout fruit development. Chlorogenic acid, phloridzin, (+)-catechin, and (?)-epicatechin were detected as polyphenolics in the skin and flesh of the three cultivars. In general, the concentrations of (+)-catechin and (?)-epicatechin in the skin and flesh of 'Redfield' were higher than those in 'Fuji' and 'Oorin'. Total phenolic concentrations on the fresh weight basis in the skin and flesh of three cultivars decreased towards the ripening stage. However, the total phenolic concentrations of 'Redfield' were higher than those of 'Fuji' and 'Oorin'. These results demonstrate that the free-radical-scavenging activity in apple skin and flesh may depend on the concentration and composition of polyphenolics.